CONSTRUCTION COMPETENCCONSTRUCTION COMPETENCY OF ISLAMIC RELIGIOUS EDUCATION IN THE HIGH SCHOOL OF ISLAMIC RELIGION AL-AMANAH JENEPONTO - Mustafa, Musram; Ondeng, Syarifuddin; Siraj, Arifuddin; Yaumi, Muhammad (Program Pascasarjana, UIN Alauddin Makassar, 2019)
This paper will elaborate on how the construction of Islamic Religious Education curriculum competencies at STAI Al-Amanah Jeneponto. This research is a qualitative research. The subject of this research is focused on the construction of the Islamic Religious Education curriculum at STAI Al-Amanah Jeneponto. The approach used in this research is sociological and pedagogical approach. The results showed that Islamic Religious Education curriculum construction at STAI Al-Amanah Jeneponto which is more focused on the design of the subject centered design curriculum, which is a curriculum designed to focus on Islamic Religious Education courses that are supported. The integration model found based on informant data is the